EAU guidelines on diagnosis and conservative management of urolithiasis - Türk, Christian; Knoll, Thomas (European urology, 2016)
Context - Low-dose computed tomography (CT) has become the first choice for detection of ureteral calculi. Conservative observational management of renal stones is possible, although the availability of minimally invasive treatment often leads to active treatment. Acute renal colic due to ureteral stone obstruction is an emergency that requires immediate pain management. Medical expulsive therapy (MET) for ureteral stones can support spontaneous passage in the absence of complicating factors. These guidelines summarise current recommendations for imaging, pain management, conservative treatment, and MET for renal and ureteral stones. Oral chemolysis is an option for uric acid stones. - Objective - To evaluate the optimal measures for diagnosis and conservative and medical treatment of urolithiasis. - Evidence acquisition - Several databases were searched for studies on imaging, pain management, observation, and MET for urolithiasis, with particular attention to the level of evidence. - Evidence synthesis - Most patients with urolithiasis present with typical colic symptoms, but stones in the renal calices remain asymptomatic. Routine evaluation includes ultrasound imaging as the first-line modality. In acute disease, low-dose CT is the method of choice. Ureteral stones <6mm can pass spontaneously in well-controlled patients. Sufficient pain management is mandatory in acute renal colic. MET, usually with α-receptor antagonists, facilitates stone passage and reduces the need for analgesia. Contrast imaging is advised for accurate determination of the renal anatomy. Asymptomatic calyceal stones may be observed via active surveillance. - Conclusions - Diagnosis, observational management, and medical treatment of urinary calculi are routine measures. Diagnosis is rapid using low-dose CT. However, radiation exposure is a limitation. Active treatment might not be necessary, especially for stones in the lower pole. MET is recommended to support spontaneous stone expulsion. - Patient summary - For stones in the lower pole of the kidney, treatment may be postponed if there are no complaints. Pharmacological treatment may promote spontaneous stone passage.
Gesehen am 30.10.2019